Incidence of deep venous thrombosis following medial opening-wedge high tibial osteotomy for varus knee osteoarthritis: a retrospective study - Shian Zhang; Chenni Ji; Song Liu; Wenxue Tong; Ling Qin; Yanbin Zhu (BMC Musculoskeletal Disorders)
Abstract Purpose Deep venous thrombosis (DVT) is a common yet underexplored complication following medial opening-wedge high tibial osteotomy (MOWHTO) for medial compartment knee osteoarthritis. Existing studies report inconsistent findings due to methodological differences and patient heterogeneity. This study aims to determine the incidence and risk factors for DVT after MOWHTO. Methods We retrospectively reviewed patients who underwent MOWHTO for medial compartment knee osteoarthritis with varus deformity between January 2019 and September 2023. Patients were classified into DVT and non-DVT groups based on Doppler ultrasonography findings. Univariate analysis was performed to compare demographics, lifestyle factors, comorbidities, surgical details, and laboratory results on postoperative day 1 between the DVT and non-DVT groups. Receiver operating characteristic (ROC) curve and area under the curve (AUC) were used to evaluate the predictive performance of laboratory indices for DVT. Multivariate logistic regression model identified independent risk factors for DVT. Results Of the 421 patients (median age: 56 years, interquartile range: 52–61 years; 146 males), 55 (13.1%) developed postoperative DVT. The incidence rates for isolated calf muscle vein thrombosis (ICMVT), deep calf vein thrombosis (DCVT), and proximal DVT was 10.7%, 1.9% and 0.5%, respectively. Most laboratory indexes demonstrated non-significant (P > 0.05) or poor (AUC < 0.70) predictive performance, except for AT III and FDP (p = 0.022, 0.033, respectively). The multivariate logistic regression analyses showed female (OR, 2.23; 95% CI, 1.09 to 4.63), diabetes (OR, 2.47; 95% CI, 1.15 to 5.40) and hyperlipidemia (OR, 1.91; 95% CI, 1.14 to 3.68) were significantly associated with postoperative DVT. Conclusion This study identified a high incidence of DVT following MOWHTO and demonstrated that female sex, diabetes and hyperlipidemia were significant risk factors. These findings may inform better risk assessment, stratification and management of DVT. Clinical trial number Not applicable.